ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI EKSPOR KOPI INDONESIA - Irmawati, Novia Salsa; Indrawati, Lucia Rita (GROWTH Jurnal Ilmiah Ekonomi Pembangunan, 2022)
The purpose of this study is to find out what factors affect Indonesian coffee exports in 2000-2021 and to find out how the impact of the shock that occurs on these factors. The research method used is descriptive quantitative method. The type of data used is secondary data in the form of time series on an annual basis from 2000-2021. The data used are sourced from the Central Statistics Agency (BPS) and Bank Indonesia. The analytical model used in this study is a multiple linear regression model with the VECM approach. The results showed that the variables of coffee production and coffee area of ​​Indonesia had a significant effect in the long term but did not significantly affect the volume of Indonesian coffee exports in the short term. The exchange rate has a negative and significant effect on the volume of Indonesian coffee exports in the long term but has no significant effect in the short term. Then, based on the results of the analysis of variance decomposition, it shows that the exchange rate variable plays the biggest role in the volatility of the volume of Indonesian coffee exports. Inflation has a significant effect in the long term but has no significant effect in the short term on the volume of Indonesian coffee exports.